Case report: Fulminant type 1 diabetes following paucisymptomatic SARS-CoV-2 infection during late pregnancy - Zhou, Lingling; Qu, Huanjia; Zhang, Qiuling; Hu, Jinhua; Shou, Lan (Frontiers in Endocrinology, 2023)
Background Dysregulation of glucose metabolism has been linked to SARS-CoV-2 infection. In addition, the occurrence of new onset diabetes mellitus, including fulminant type 1 diabetes, has been reported after SARS-CoV-2 infection or vaccination. Methods and results A young Chinese woman in her last trimester of pregnancy presented with an abrupt progression of hyperglycemia and ketoacidosis, but with a near-normal glycohemoglobin level following paucisymptomatic SARS-CoV-2 infection. The low C peptide levels, both fasting and postprandial, reflected profound insulin deficiency in the setting of negative islet autoantibody testing, consistent with a diagnosis of fulminant type 1 diabetes. Ketoacidosis and hyperglycemia quickly improved following the introduction of insulin therapy, but not the β cell function. The patient received treatment with insulin pump therapy after being discharged, and the first follow-up revealed a well-controlled glucose profile. Conclusions New-onset FT1D can occur after SARS-CoV-2 infection. Our report raises awareness of this rare but serious situation, promoting early recognition and management of FT1D during the COVID-19 pandemic.